Point-of-Care Ultrasound for Targeted Assessment of Shock: Remember HIPP in Children. Issue 8 (August 2019) - Weberding, Nathaniel T.; Marin, Jennifer R.
Abstract : Abstract: The differential diagnosis for patients presenting in shock can be broad, making rapid diagnosis and management challenging. We present a case of a medically complex patient with presumed septic shock, diagnosed with a large pericardial effusion with evidence of tamponade using the rapid ultrasound in shock and hypotension protocol. The point-of-care ultrasound examination allowed for more timely and definitive management. Abstract : Supplemental digital content is available in the text.